SURFACE-STRUCTURE AND INERT SURFACE CHARACTERISTICS OF PERFLUORODECANOIC ACID-GRAFTED POLYURETHANE - HAN, DK; JEONG, SY; KIM, YH; MIN, BG (JOHN WILEY & SONS INC, 1993)
The surface compositions and characteristics of perfluorodecanoic acid (PFDA) -grafted polyurethane (PU) were investigated to understand its enhanced blood compatibility. The grafting of PFDA was identified by attenuated total reflectance-Fourier transform infrared (ATR-FTIR). The results from angular-dependent electron spectroscopy for chemical analysis (ADESCA) demonstrated the fluorocarbon enrichment at the outermost layer in PFDA-grafted PU. Static secondary ion mass spectroscopy (SIMS) experiments supported the results drawn from ATR-FTIR and ADESCA data about the surface compositions. Energy-dispersive X-ray analysis (EDXA) data by fluorine mapping also indicated a considerable coverage with fluoroalkyl groups on the PU-PFDA surface. The critical surface tension, gamma(c), of the highly hydrophobic PU-PFDA surface revealed an extremely low value of 6.9 dyn/cm due to the optimal orientation of -CF3 groups to the uppermost surface. Therefore, such an inert low-energy surface may contribute to improve blood compatibility of PFDA-grafted PU.